2005
DOI: 10.1121/1.1848011
|View full text |Cite
|
Sign up to set email alerts
|

Pitch (F0) and formant profiles of human vowels and vowel-like baboon grunts: The role of vocalizer body size and voice-acoustic allometry

Abstract: Key voice features--fundamental frequency (F0) and formant frequencies--can vary extensively between individuals. Much of the variation can be traced to differences in the size of the larynx and vocal-tract cavities, but whether these differences in turn simply reflect differences in speaker body size (i.e., neutral vocal allometry) remains unclear. Quantitative analyses were therefore undertaken to test the relationship between speaker body size and voice F0 and formant frequencies for human vowels. To test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
181
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(192 citation statements)
references
References 50 publications
10
181
0
Order By: Relevance
“…In mammals, this correlation was tested and corroborated for various frequency parameters, such as mean fundamental frequency F0 (Zimmermann 1995;Tembrock 1996;Pfefferle and Fischer 2006), dominant frequency (the frequency with maximum amplitude in the spectrum of a vocalization) (Nikolskij 1984;Jones 1996Jones , 1999Fletcher 2004Fletcher , 2007, frequency bandwidth/range (Hauser 1993(Hauser , 1996, mean repertoire frequency (Hauser 1993), and formants (vocal tract resonance frequencies) (Fitch 1997;Riede and Fitch 1999). There are, however, a few published examples of vocalizations in mammals and in other vertebrate groups for which certain pertinent frequency parameters tested are not negatively correlated with body size/weight, in both intraspecific (Masataka 1994;Riede and Fitch 1999;Rendall et al 2005) as well as interspecific comparisons (Hauser 1993(Hauser , 1996Zimmermann 1995;Laiolo and Rolando 2003). Fitch (1997Fitch ( , 2000 set out the correlation between body size and formants in detail, and termed it ''acoustic allometry.'…”
Section: Scaling Effectmentioning
confidence: 99%
“…In mammals, this correlation was tested and corroborated for various frequency parameters, such as mean fundamental frequency F0 (Zimmermann 1995;Tembrock 1996;Pfefferle and Fischer 2006), dominant frequency (the frequency with maximum amplitude in the spectrum of a vocalization) (Nikolskij 1984;Jones 1996Jones , 1999Fletcher 2004Fletcher , 2007, frequency bandwidth/range (Hauser 1993(Hauser , 1996, mean repertoire frequency (Hauser 1993), and formants (vocal tract resonance frequencies) (Fitch 1997;Riede and Fitch 1999). There are, however, a few published examples of vocalizations in mammals and in other vertebrate groups for which certain pertinent frequency parameters tested are not negatively correlated with body size/weight, in both intraspecific (Masataka 1994;Riede and Fitch 1999;Rendall et al 2005) as well as interspecific comparisons (Hauser 1993(Hauser , 1996Zimmermann 1995;Laiolo and Rolando 2003). Fitch (1997Fitch ( , 2000 set out the correlation between body size and formants in detail, and termed it ''acoustic allometry.'…”
Section: Scaling Effectmentioning
confidence: 99%
“…ΔF also seems to moderately correlate with speakers' body size, and in particular men's height (Evans et al, 2006;Greisbach, 2007;Rendall et al, 2005; but see Van Dommelen and Moxness, 1995), with taller men speaking with lower ΔF. However, there appears to be no consistent relationship between stature and F0 within sexes: while two studies have reported significant correlations between height and F0 (Graddol and Swann, 1983;Puts et al, 2012), other studies have failed to identify such a relationship (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, despite its dependence on the length, mass and tension of vocal folds (Titze 1994), in mammals the fundamental frequency of vocalizations does not consistently provide reliable information on body size (Lass & Brown 1978;Reby & McComb 2003a;Rendall et al 2005; but see Pfefferle & Fisher 2006). Nevertheless, F0 remains a highly distinctive and variable component of mammal calls and its covariation with caller attributes suggests that it might nonetheless provide important information for receivers in sexual contexts (e.g.…”
Section: Introductionmentioning
confidence: 99%